Phase Boundary Mapping in ZrNiSn Half-Heusler for Enhanced Thermoelectric Performance - Xiaofang Li; Pengbo Yang; Yumei Wang; Zongwei Zhang; Dandan Qin; Wenhua Xue; Chen Chen; Yifang Huang; Xiaodong Xie; Xinyu Wang; Mujin Yang; Cuiping Wang; et al. (Research, 2020)
The solubility range of interstitial Ni in the ZrNi1+xSn half-Heusler phase is a controversial issue, but it has an impact on the thermoelectric properties. In this study, two isothermal section phase diagrams of the Zr-Ni-Sn ternary system at 973 K and 1173 K were experimentally constructed based on the binary phase diagrams of Zr-Ni, Zr-Sn, and Ni-Sn. The thermodynamic equilibrium phases were obtained after a long time of heating treatment on the raw alloys prepared by levitation melting. Solubilities of x<0.07 at 973 K and x<0.13 at 1173 K were clearly indicated. An intermediate-Heusler phase with a partly filled Ni void was observed, which is believed to be beneficial to the lowered lattice thermal conductivity. The highest ZT value~0.71 at 973 K was obtained for ZrNi1.11Sn1.04. The phase boundary mapping provides an important instruction for the further optimization of ZrNiSn-based materials and other systems.